Miscalibrations in judgements of attractiveness with cosmetics. Issue 10 (October 2014) - Jones, Alex L.; Kramer, Robin S. S.; Ward, Robert
Women use cosmetics to enhance their attractiveness. How successful they are in doing so remains unknown—how do men and women respond to cosmetics use in terms of attractiveness? There are a variety of miscalibrations where attractiveness is concerned—often, what one sex thinks the opposite sex finds attractive is incorrect. Here, we investigated observer perceptions about attractiveness and cosmetics, as well as their understanding of what others would find attractive. We used computer graphic techniques to allow observers to vary the amount of cosmetics applied to a series of female faces. We asked observers to optimize attractiveness for themselves, for what they thought women in general would prefer, and what they thought men in general would prefer. We found that men and women agree on the amount of cosmetics they find attractive, but overestimate the preferences of women and, when considering the preferences of men, overestimate even more. We also find that models' self-applied cosmetics are far in excess of individual preferences. These findings suggest that attractiveness perceptions with cosmetics are a form of pluralistic ignorance, whereby women tailor their cosmetics use to an inaccurate perception of others' preferences. These findings also highlight further miscalibrations of attractiveness ideals.